The last way home [large type] - Johnson, Liz, 1981- (Johnson, Liz, 1981- Prince Edward Island shores, 2022)
"When Eli Ross left Prince Edward Island to join the NHL, he left a broken family behind. More than a decade later, he's broke and headed home to an uncertain welcome. He wants to make things right with the family he wronged, but his mom's business partner isn't making it easy. To top it off, the coaching job he's accepted turns out to be far more difficult than he anticipated.For years, Violet Donaghy has put everything she had into making Eli's mom's ceramics shop a success, and she's not eager to forgive the man who hurt the family that's taken her in as one of their own. But when the kiln at the shop starts a fire that nearly destroys the studio, she'll need all the help she can get to save the business and their summer income.Can these two strong-willed people come together to mend the broken pieces of the Ross family? Or will the ghosts of the past continue to haunt them?Return to Prince Edward Island for a romantic story of family, forgiveness, and the power of love"--